Power transformers winding fault diagnosis by the on-load exciting current extended Park's vector approach - Oliveira, L. M. R. (2014)
This paper presents the application of the on-load exciting current Extended Park's Vector Approach to diagnose incipient turn-to-turn winding faults in operating power transformers. Experimental and simulation test results demonstrate the effectiveness of the proposed technique, which is based on the spectral analysis of the AC component of the on-load exciting current Park's Vector modulus.